KAJIANEKOLOGISPASIALBENTANGLAHANUNTUKKELESTARIANSITUSSEJARAHDIKECAMATANIMOGIRIDANKRETEKKABUPATENBANTUL - Nurul Khotimah (Universitas Negeri Yogyakarta, 2012)
Landscapeecologyapproachisneededtoinventarizedthehistoricsite,environmentalproblemthatbemakemanagementconstraint,regionpotention,alsodirectionandmanagementpriority,anddevelopmentofhistoricsitesaspopulartourismarea.Theresultoftheresearchshowsthat:(1)HistoricsitesatImogiriDistrictspreadatGirirejo,Wukirsari,Karangtengah,Selopamioro,andImogiriVillages,meanwhileatKretekDistrictgatheringroupatParangtritisVillage;(2)WholelandstatusofhistoricsitesmeansSultangroundlandstatus,withlandprocessingthatisdonebyaroundcommunityforfield,communityforest,miningofCdiggingmaterial,housing,homestay,shop/smallshopthatcanmakethreatenhistoricsitescontinuitythatexist;(3)Theproblemsofenvironmentaroundhistoricsitescanbephysicalandsocialenvironment;and(4)Foranticipatingitneedsmakinghistoricsitescontinuityorganizationorinstitutiontoorganizeandsupportedecosystemapproachastheefforttorganizeanddevelopedthehistoricsitesaspopulartourismplaces.KeyWord:spatialecology,historicsites,continuity